TYPES OF COPULA VERB IN INDONESIAN LANGUAGE - Pawestri, Norma (Universitas Esa Unggul, 2019)
AbstractThis study tries to discuss and analyze the topic of copula verbs in Indonesian language, and is aimed to see the types of copula verbs in Indonesian language, also the structure of copula verb in Indonesian language. This research used descriptive analysis method, the findings showed that in Indonesian language, there are these copula verbs such as adalah or ialah which equals to to be in English, but unlike in English, these copula verbs are optional in Indonesian language. Just like in English, it is imperative to use the copulative verbs such as: seem (tampak /terlihat, appear (tampak), become (menjadi), turn (berubah) to form a contruction in Indonesian language, but unlike in English, the form of copula in Indonesian language never changes based on tenses. Another similarity of Indonesian language and English is the necessity to use the copulative verbs such as: feel (merasa), look (tampak/terlihat) etc to form a construction. It is also possible in Indonesian language to form a copula verb by creating the verb into a noun and add some prefix and suffix nya and pair it with adjective. Keywords: copula verb, indonesian language, english AbstrakPenelitian ini mencoba membahas dan menganalisis kata kerja kopula dalam bahasa Indonesia dan bertujuan untuk mengetahui tipe dan struktur kata kerja kopula dalam bahasa Indonesia. Penelitian ini menggunaan metode deskriptif analisis dan hasilnya menujukkan bahwa dalam bahasa Indonesia, terdapat beberapa kata kerja kopula seperti adalah atau ialah yang setara penggunaannya dengan to bedalam bahasa Inggris, namun yang membedakan adalah bahwa penggunaan kata kerja tersebut tidak lah krusial dalam bahasa Indonesia. Sama halnya dengan dalam bahasa Inggris beberapa kopula seperti tampak/terlihatâ(seem), tampak (appear), menjadi (become), berubah (turn) membentu konstruksi pada bahasa Indonesia, namun dalam bahasa Indonesia, kata kerja kopula tersebut tidak di pengaruhi tenses. Kata kunci: Kata kerja copula, bahasa indonesia, bahasa inggris